Uji Efek Anti-Inflamasi dan Analgesik dari Rebusan Daun Bambu Kuning (Bambusa vulgaris Schard) - Sondang Khairani; Lestari Rahayu; Ni Made Sandhiutami; Rika Sari Dewi; Ita Rahmawati (Fakultas Farmasi Universitas Pancasila, 2021)
Bamboo Kuning (Bambusa vulgaris Shard) leaves its efficacy as antioxidant, anti-inflammation, antidiabetic and antiulcer. The study aims to know volume edema decrease of rats foot as anti-inflammatory effect and the amount of strectching mice an analgesic effect the decoction of Bamboo Kuning. Anti-inflammatory test used Winter methods. Rats were be diveded into 5 groups: negative control be given aquadest, positive control be given sodium diclofenac 4,367 mg/200g BB, the test groups were given the decoction of Bamboo Kuning leaves 2,8 mL/200g BB with a concentration of 10%, 20% and 40%. Analgesic testing used methods Sigmund. Mice were divided into 5 groups: negative control be given aquadest, positive control were given sodium diclofenak 0,26 mg/20g BB, the test group was given the boiled of bamboo kuning leaves 0,4 mL/20g BB with concentration 10%, 20% and 40%. Statistic result decoction of leaves Bamboo Kuning dose 2,8 mL/200g BB with concentration 10%, 20% and 40% have anti-inflammatory and analgesic effect. Decoction of Bamboo Kuning leaves dose 2,8 mL/200g BB with concentration of 10%, 20% and 40% have anti-inflammatory and analgesic effect are lower than sodium diclofenac. Increased dose boiled of Bamboo Kuning leaves no provide increased effect as an anti-inflammatory and analgesic.